Effects of Co-Feeding Dry and Live Feed from the Onset of Exogenous Feeding on Red Seabream Pagrus major Larviculture and Pre-Growing - Sofia Brinkmann Bougali; Nafsika Karakatsouli; Kostas Ntomalis; Anemos Kastelis; Vasiliki-Anna Alexopoulou; Alkisti Batzina; Isidoros Markakis (Fishes, 2025)
Current feeding protocols used in commercial hatcheries of Mediterranean fish species are, for a species-dependent period after hatching, based on live feeds which have often raised issues of biosecurity, stability, availability, price and nutrients content. Instead, dry feeds can offer stability in nutritional value, price and supply. The aim of the present study was to evaluate an alternative feeding protocol by co-feeding live and dry feed at first feeding red seabream larvae (on 3 days post-hatching—3 dph, DF3) and to compare it to a standard feeding protocol (i.e., dry feed introduced on 22 dph, DF22). Larvae productivity and functional development of the digestive system were evaluated under actual production conditions in a commercial hatchery. Additionally, post-larvae efficiency during pre-growing was evaluated under controlled laboratory conditions. The results obtained showed that the experimental protocol (DF3) promoted larval growth without affecting larval survival and the efficiency of the digestion processes. After pre-growing, DF3-produced juveniles showed a decreased incidence of spinal cord malformations, while the initially gained growth advantage was maintained. The present study shows the feasibility of an alternative feeding protocol for red seabream intensive larviculture and points out the critical role that larval rearing may have for later production stages.